Improving Studentsâ€™ Speaking Ability through Small Group Discussion - Matondang, Marhaeni K. D; Silalahi, Tiodora F; Siahaan, Tumpal (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research is a quantitative descriptive study that explains the improvement of students' speaking ability through small discussion .It is very effective to apply in the classroom because it can improve the students to achieve specific objectives permits students to assume more responsibility for their own learning, develop social and leadership skills and become involved in an alternative instructional approach.â€ Small group can help students to communicate the ideas to each other meaningfully. Besides, small group can develop students' team working abilities. Students can increase their self-esteem, social interaction, and even their motivation to learning English. The data showed that in the posttest have better enhancement than pretest. For both test, there was nobody classified into very bad. Most the students in pretest were classified into enough and bad score. In posttest, 3 students got very good score and 8 students got good score. It means, in the posttest the effect has been seen after using treatment (small group discussion).